Determinantes do comportamento alimentar de idosos jovens e longevos do Rio Grande do Sul - Palma, Shelly Westphalen (2018)
Behavior can vary at different stages of life, as influences are constantly changing. When children feed by intuition, as adults by beliefs, attitudes and cognitions. It is believed that these changes manifest themselves differently among the young and long-lived elderly. The objective of this study was to evaluate the determinants of the eating behavior of the young and long-lived elderly, as well as to identify and describe the sociodemographic characteristics and health conditions of the elderly and associate them to the eating behavior. This is a quantitative, analytical cross-sectional study with analysis of secondary data from the survey "Perfil dos Idosos do Rio Grande do Sul", 2010. The study sample consisted of 6974 elderly men and women aged 60 years or more, from urban and rural areas of Rio Grande do Sul. Elderlies patients with cognitive status or weakened clinical condition were not included and the questionnaires answered by the companions did not participate in the analysis of this study. The collection was performed through a home interview using a questionnaire with 72 simple and multiple-choice questions. For the analysis of the food behavior the variables evaluated were: functional difficulty to feed themselves, self-perception of appetite and number of daily meals. The sociodemographic variables analyzed were: age, sex, marital status, schooling, income, residence in urban or rural areas and the frequency of leaving home, which were also used to characterize the sample. In order to evaluate the health conditions, the following variables were analyzed: self-perception of health; self-perception of oral health, vision and hearing, nutritional status and chronic diseases. Student's t, Mann-Whitney, Pearson's Chisquare and Fischer's exact tests (p<0.05) were performed in the univariate and adjusted analysis the Poisson regression model. All the elderly agreed to participate in the study by signing the Informed Consent Term. The largest research was approved by the Research Ethics Committees of the School of Public Health of the State of Rio Grande do Sul and the Pontifical Catholic University of Rio Grande do Sul. The results obtained showed that young adults fed more easily (p<0.001) and had better self-perception of appetite (p=0.019); older people had more daily meals (p=0.022). To be long-lived (p<0.001), to live without a partner (p=0.006), to live in rural areas (p=0.034), to have worse self-perception of health and oral health (p<0.001) increased the functional difficulty to feed alone. The higher the income, the better the self-perception of appetite (p=0.043); the worse the selfperception of health (p≤0.004) and hearing (p=0.014), the worse the self-perception of appetite. Being long-term (p=0.049), leaving home less (p=0.044), regular self-perception of oral health (p=0.001) and having chronic diseases (p<0.001) were associated with higher daily meals, but self- regular hearing was associated with fewer daily meals (p<0.001). It was concluded that the young adults presented better food behavior and that the factors determining the worst food behavior were to be long-lived, to live without a partner, to live in rural areas, worse self-perception of health, oral health and hearing.